Land use intensity controls the diversity-productivity relationship in northern temperate grasslands of China - Yan, Yidan; Xu, Lijun; Wu, Xinjia; Xue, Wei; Nie, Yingying; Ye, Liming (Frontiers in Plant Science, 2023)
The diversity-productivity relationship is a central issue in maintaining the grassland ecosystem’s multifunctionality and supporting its sustainable management. Currently, the mainstream opinion on the diversity-productivity relationship recognizes that increases in species diversity promote ecosystem productivity. Here, we challenge this opinion by developing a generalized additive model-based framework to quantify the response rate of grassland productivity to plant species diversity using vegetation survey data we collected along a land-use intensity gradient in northern China. Our results show that the grassland aboveground biomass responds significantly positively to the Shannon-Wiener diversity index at a rate of 46.8 g m-2 per unit increase of the Shannon-Wiener index in enclosure-managed grasslands, under the co-influence of climate and landscape factors. The aboveground biomass response rate stays positive at a magnitude of 47.1 g m-2 in forest understory grassland and 39.7 g m-2 in wetland grassland. Conversely, the response rate turns negative in heavily grazed grasslands at -55.8 g m-2, transiting via near-neutral rates of -7.0 and -7.3 g m-2 in mowing grassland and moderately grazed grassland, respectively. These results suggest that the diversity-productivity relationship in temperate grasslands not only varies by magnitude but also switches directions under varying levels of land use intensity. This highlights the need to consider land use intensity as a more important ecological integrity indicator for future ecological conservation programs in temperate grasslands.